2018
DOI: 10.1111/1749-4877.12301
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and space use of seed‐dispersing rodents in central Pyrenees: implications for genetic diversity, conservation and plant recruitment

Abstract: The function and conservation of many forest ecosystems depend on the distribution and diversity of the community of rodents that consume and disperse seeds. The habitat preferences and interactions are especially relevant in alpine systems where such granivorous rodents reach the southernmost limit of their distribution and are especially sensitive to global warming. We analyzed the community of granivorous rodents in the Pyrenees, one of the southernmost mountain ranges of Europe. Rodent species were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…As a study model we have used a well-documented plant-disperser-predator assemblage: holm oak (Quercus ilex) acorns, which are consumed and dispersed by wood mouse (Apodemus sylvaticus), that in turn is the main prey of the common genet (Genetta genetta). The wood mouse is the most abundant scatter-hoarding rodent in Mediterranean areas of southern Europe, distributed from the Iberian Peninsula to southwestern Asia and the Himalayas, and from northwestern Africa to the south of Scandinavia (Torre et al, 2002;Urgoiti et al, 2018). This nocturnal and small rodent (15-35g) is a prominent consumer and disperser of acorns during the seeding season in autumn, influencing the recruitment dynamics of many oak species (den Ouden et al, 2005;Sunyer et al, 2015), like the holm oak, which is the most widespread oak in the Mediterranean basin (Blondel & Aronson, 1999).…”
mentioning
confidence: 99%
“…As a study model we have used a well-documented plant-disperser-predator assemblage: holm oak (Quercus ilex) acorns, which are consumed and dispersed by wood mouse (Apodemus sylvaticus), that in turn is the main prey of the common genet (Genetta genetta). The wood mouse is the most abundant scatter-hoarding rodent in Mediterranean areas of southern Europe, distributed from the Iberian Peninsula to southwestern Asia and the Himalayas, and from northwestern Africa to the south of Scandinavia (Torre et al, 2002;Urgoiti et al, 2018). This nocturnal and small rodent (15-35g) is a prominent consumer and disperser of acorns during the seeding season in autumn, influencing the recruitment dynamics of many oak species (den Ouden et al, 2005;Sunyer et al, 2015), like the holm oak, which is the most widespread oak in the Mediterranean basin (Blondel & Aronson, 1999).…”
mentioning
confidence: 99%
“…In rodents, the D-loop has been useful in phylogenetic analyses due to its elevated mutation rate, lack of recombination and maternal inheritance (Robins et al 2014). Also, due to its high mutation rate, this marker has been used to detect signatures of population structure at a scale of just a few kilometers (Hirota et al 2004;Urgoiti et al 2018). The PCR reactions contained 14.85 μL DEPC H2O, 3.0 μL 10X Reaction buffer, 3.0 μL deoxynucleotide triphosphates (dNTPs, 2 mM of each), 1.5 μL each forward and reverse primer (10 μM), 3.0 μL of 0.1 % bovine serum albumin (BSA), 0.15 μL Ampli-Taq DNA polymerase (Applied Biosystems, Foster City, CA), and 3 μL of DNA for a final reaction volume of 30 μL.…”
Section: Methodsmentioning
confidence: 99%
“…Bogdziewicz et al (2018), working in oak forests of Europe, demonstrated how the invasive red oak (Q. rubra) is nearly free of insect seed predators compared with a common native oak (Q. petrea) in Europe and, as a result, afforded significant dispersal and regeneration advantages over the native species. Urgoiti et al (2018) explored the distribution of small-mammal communities and genetic isolation of two keystone seed dispersers in the Pyrenees Mountains of Europe. Their results hold important implications for how geographic variation in seed consumers influences native plant dispersal and how global warming will likely influence isolation of these keystone seed dispersers.…”
Section: Editorialmentioning
confidence: 99%